Sistem Monitoring Akademik Mahasiswa Difabel dengan Black Box Testing - Syifaun Nafisah; Siti Rohaya (PLD UIN Sunan Kalijaga, 2021)
The web-based Academic Monitoring System for Students with Disabilities is a software development that aims to monitor the academic activities of students with disabilities. This development needs to be done because the average Grade Point Average (GPA) of students with disabilities is often below the average GPA of their class. This system was developed using the R&D method with a prototyping approach. Based on testing with black box techniques that have been carried out, this system shows the accuracy of success, with feature suitability and user acceptance of the system by 100%. In conclusion, this system can be used as a software tool to monitor the academic activities of students with disabilities.[Sistem Monitoring Akademik bagi Mahasiswa Difabel berbasis web merupakan sebuah pengembangan software yang bertujuan untuk melakukan monitoring kegiatan akademik para mahasiswa penyandang disabilitas. Pengembangan ini perlu dilakukan karena rerata Indeks Prestasi Kumulatif (IPK) mahasiswa penyandang disabilitas sering kali di bawah rerata IPK seangkatan. Sistem ini dikembangkan dengan metode R&D dengan pendekatan prototyping. Berdasar pengujian dengan teknik black box yang telah dilakukan, sistem ini menunjukkan tingkat akurasi keberhasilan, dengan kesesuaian fitur dan penerimaan user terhadap sistem sebesar 100%. Kesimpulannya, sistem ini dapat dimanfaatkan sebagai perangkat lunak bantu untuk melakukan monitoring terhadap proses kegiatan akademik para mahasiswa difabel.]